Principal’s Strategies in Developing Student Leadership Competencies Through Service Learning in Elementary Schools - Mohammad Bilutfikal Khofi; Ahmad Sunoko (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Elementary education is pivotal in shaping character and cultivating leadership competencies for students' future lives. This study examines how the principal implements service-learning strategies to foster student leadership at Taman Bondowoso State Elementary School. The research uses a qualitative approach to explore managerial practices integrating community-based learning with leadership development. Data was collected through observations, indepth interviews, and document analysis involving seven informants: the school principal, four teachers, and two students purposively selected for active involvement in service-learning activities. The findings reveal five key service-learning strategies: (1) structured class discussions to enhance critical thinking and communication, (2) collaborative group projects that emphasize shared responsibility and peer leadership, (3) role-modeling inspired by local and historical figures to instill values such as justice and empathy, (4) extracurricular programs that develop social and organizational skills, and (5) community service that teach social responsibility through hands on experiences. These strategies demonstrate how service-learning bridges academic goals with real world leadership applications, offering a replicable model for elementary education focused on character and leadership development.